Early public childcare and fertility: A longitudinal study for Europe - Giovanni Minchio; Agnese Vitali; Stefani Scherer (PLoS ONE, 2026)
Empirical research reveals a considerable mismatch between desired and actual fertility across Europe, a mismatch which is more pronounced in countries characterized by limited policy support for families, suggesting that institutional interventions might be relevant in reducing this gap. This study analyzes the association between one of such policy interventions, namely public early childcare and education services (ECEC, age 0–2), and childbearing. The expectation is that an increase in the provision of public early childcare service in the region of residence will be positively associated with fertility. While existing evidence on whether childcare expansion increases fertility comes primarily from single-country studies or national-level comparisons, our empirical analysis combines sub-national information on regional public early childcare with longitudinal micro-level data from the European Union Statistics on Income and Living Conditions, from 2005 to 2020. Results show that an increase in regional ECEC is associated with higher probability of experiencing both transition to first and second birth and this association is significantly stronger in regions where ECEC was initially lower. Associations between childcare expansions and first birth transitions are particularly pronounced among lower-educated or employed women, while associations with second birth transitions are similar across all socio-economic groups, yet statistically non-significant among lower-educated mothers. Our results suggest that investing in public childcare is associated, in the short term, with reducing the gap between intended and actual fertility in Europe, particularly in contexts where provision is lower.